Model-predictive control based on Harris Hawks optimization for split-source inverter - Youssuf Ahmed Elthokaby; Ibrahim Abdelsalam; Naser Abdel-Rahim; Islam Mohamed Abdealqawee (Institute of Advanced Engineering and Science, 2022)
This paper proposed a modified algorithm for controlling a single-phase split-source inverter. The proposed algorithm is a modified model predictive control based on Harris Hawks optimization, where the AC output voltage, the DC-link voltage, and the DC input current are controlled within one cost function. Hence, the discrete time models of both AC-side and DC-side are obtained. For proper operation of the modified MPC, each error term within the cost function has a weighting factor. Harris Hawks optimization technique is used to determine the weighting factors at each term of the cost function. The proposed algorithm is validated using MATLAB/Simulink. Simulation results show that the system has succeeded in controlling AC load voltage, input current, and achieving constant DC-link voltage over a wide operating range.